Digital ethnography: ethics through the case of QAnon - Cera, Michelle (Frontiers in Sociology, 2023)
Digital ethnography is a relatively new practice with unclear standards and guidelines. As a result, the ethics of the practice remain unclear. Scholarly debates have emerged surrounding the decision of many researchers and institutional review boards to treat social media data as public. Concerns have also been raised about how informed consent can be adapted to online fieldwork. How does a researcher make their presence known when they are not visible in the traditional sense? Which online interactions should be considered public, and which are private? How can we protect the anonymity of social media users? This article leverages original research on QAnon social media spaces to suggest ethical guidelines for digital ethnographic practices. It begins with an overview of scholarly debates on the ethics of digital ethnography. It then advocates for rethinking the public-private binary as it applies to the digital world, ameliorating the “lurker” concern by making the presence of the researcher known in appropriate spaces, and maintaining the integrity of the data by avoiding reconstruction. Although many digital ethnographers have chosen to reconstruct or paraphrase online data to protect privacy, this practice comes with its own ethical dilemmas. This article also discusses several issues with institutional review boards and suggests important changes. The ethical dilemmas and guidance discussed in this article are critical lessons for digital and in-person ethnographers alike.